2014
DOI: 10.1099/mic.0.070763-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a bacterial catalase in a strictly anaerobic methanogen significantly increases tolerance to hydrogen peroxide but not oxygen

Abstract: Haem-dependent catalase is an antioxidant enzyme that degrades H2O2, producing H2O and O2, and is common in aerobes. Catalase is present in some strictly anaerobic methane-producing archaea (methanogens), but the importance of catalase to the antioxidant system of methanogens is poorly understood. We report here that a survey of the sequenced genomes of methanogens revealed that the majority of species lack genes encoding catalase. Moreover, Methanosarcina acetivorans is a methanogen capable of synthesizing ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…We next searched for examples of heme b -dependent proteins shown in a widescale study of diverse bacterial genomes to be broadly distributed in aerotolerant anaerobes ( 88 ), since these might also be prevalent in aerotolerant archaeal methanogens, methanotrophs, and alkanotrophs. KatG is a heme b -dependent catalase-peroxidase that is known to be critical for H 2 O 2 detoxification in aerobes ( 89 ) and has been identified in multiple anaerobes (including Methanosarcina acetivorans ) ( 90 ). Cytochrome bd oxidase (Cyt bd ) is a terminal respiratory oxidase with high affinity for extremely low quantities of O 2 in the obligate anaerobic bacteria Bacteroides fragilis and Desulfovibrio gigas ( 91 , 92 ).…”
Section: Resultsmentioning
confidence: 99%
“…We next searched for examples of heme b -dependent proteins shown in a widescale study of diverse bacterial genomes to be broadly distributed in aerotolerant anaerobes ( 88 ), since these might also be prevalent in aerotolerant archaeal methanogens, methanotrophs, and alkanotrophs. KatG is a heme b -dependent catalase-peroxidase that is known to be critical for H 2 O 2 detoxification in aerobes ( 89 ) and has been identified in multiple anaerobes (including Methanosarcina acetivorans ) ( 90 ). Cytochrome bd oxidase (Cyt bd ) is a terminal respiratory oxidase with high affinity for extremely low quantities of O 2 in the obligate anaerobic bacteria Bacteroides fragilis and Desulfovibrio gigas ( 91 , 92 ).…”
Section: Resultsmentioning
confidence: 99%
“…The activation of MaMsvR DNA binding by MaTrx7 also integrates P msvR regulation by MsvR into the physiology of M. acetivorans , which supports the future use of P msvR in engineering oxidant-responsive gene expression strains. For example, we have previously demonstrated that increased expression of catalase protects M. acetivorans from H 2 O 2 [16]. …”
Section: Resultsmentioning
confidence: 99%
“…The correlation between these two attributes is statistically significant (metabolism PAH degrading, C OG 1592 , 0.72, < 2.2 • 10 −16 ). The usage of rubrerythrin in anaerob bacteria has been confirmed (Jenney et al 1999;Lumppio et al 2001;Jennings et al 2014) in the process of degrading O − 2 and H 2 O 2 without producing O 2 . The attribute (hyperthermophil, archaeal, hydrotherm, vent, heterotroph), is significantly associated (co-occurring in 37 redescriptions) and correlated with attribute C OG 3351 (putative archaeal flagellar protein D/E), ((hyperthermophil, archaeal, hydrotherm, vent, heterotroph), C OG 3351 , 0.49, < 2.2 • 10 −16 ).…”
Section: Exploring Redescriptions Obtained On the Phenotype Datasetmentioning
confidence: 89%